Planejamento em unidades de informação: um estudo exploratório da apropriação do planejamento em Biblioteconomia e Ciência da Informação - Solange Madalena Souza Macedo (2019)
The units of information are administrative instances that aim at the qualified use of the information, through activities of organization of the information and production of services and informational products. To do so, it is necessary to manage the processes and services mentioned, which requires the optimization of resources, by measuring the variables involved, such as cost and time. One of the management actions is planning, whose validity involves an early decision making, in the perspective that the future can be improved by means of an intervention at the present time. The research object is the planning in units of information, as a process that enhances the access and qualified use of the information by the user. The problematization is related to the presupposition of theoretical gap, leading to the question about how the appropriation of the planning occurs to the context of the units of information in the literature of the area. The objective of the research is to explore the planning in units of information in the literature, from the literature in the area of Librarianship and Information Science, identifying categories that support reflections on knowledge of this subject.The objective of this research is to explore the planning in information units in the literature, from the literature in the area of Librarianship and Information Science, identifying categories that support reflections on knowledge of this subject.The specific objectives are: considering that the subject requires appropriation of the advances of the Administration area, systematize general studies on management and specific about planning that allow to base and validate the knowledge about the theme of the thesis; discourse the contents that make it possible to make explicit the planning in information units, in the literature area of Library and Information Science, in their main characteristics; identify and systematize representative categories of the literature on planning in information units, in order to obtain parameters for the elaboration of reflections on the knowledge produced.The research is of the exploratory and descriptive type, regarding the purposes that it was proposed, and bibliographical about the means or procedures adopted. The research technique used was the indirect documentation of the bibliographic type. An important aspect that the research evidences is the need of the diagnostic evaluation of the unit of information for the implementation of the planning. The research showed that there is a theoretical gap in Brazil on the subject, given the recurrence of studies patterned to the transfer, that by appropriation, citing many Administration texts, unlike studies from other countries, especially the Spanish and North American, which also use authors from the area of Library and Information Science, who appropriated the planning to the context of the information units. Thus, the research allowed to observe, through the systematization of representative categories of the literature on planning in information units, the appropriation of planning to the area of Library and Information Science.